2021
DOI: 10.1182/blood.2020006770
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with outcomes after a second CD19-targeted CAR T-cell infusion for refractory B-cell malignancies

Abstract: CD19-targeted chimeric antigen receptor-engineered (CD19 CAR) T cell therapy has shown significant efficacy for relapsed or refractory (R/R) B-cell malignancies. Yet CD19 CAR T cells fail to induce durable responses in most patients. Second infusions of CD19 CAR T cells (CART2) have been considered as a possible approach to improve outcomes. We analyzed data from 44 patients with R/R B-cell malignancies (ALL, n=14; CLL, n=9; NHL, n=21) who received CART2 on a phase 1/2 trial at our institution. Despite a CART2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(103 citation statements)
references
References 40 publications
3
100
0
Order By: Relevance
“…Clinical trials have precisely reported little to no success of reinfusions [15,16,63], which could also be related to the lack of lymphodepleting chemotherapy and/or the role of regulatory T-cells. A recent study identified the factors associated with complete response after second infusions [64]. These are mainly a higher dose, as reported here, and lymphodepleting chemotherapy before the first dose.…”
Section: Discussionsupporting
confidence: 53%
“…Clinical trials have precisely reported little to no success of reinfusions [15,16,63], which could also be related to the lack of lymphodepleting chemotherapy and/or the role of regulatory T-cells. A recent study identified the factors associated with complete response after second infusions [64]. These are mainly a higher dose, as reported here, and lymphodepleting chemotherapy before the first dose.…”
Section: Discussionsupporting
confidence: 53%
“…The extent of the role of ADA in this setting will need to be ascertained in a larger cohort of patients in the future. Previously, a large study evaluating CD19targeted CAR T-cell therapy in B-cell malignincies showed that addition of fludarabine to cyclophosphamide-based lymphodepletion before the first infusion and an increased dose in the second infusion compared to the first infusion would increase the response rate 16 , both of which were followed in the currect study.…”
Section: Discussionmentioning
confidence: 99%
“…These clinical observations provide further validity of adopting a systems approach while developing translational PK-PD relationships for CAR-T cells. 31 Some other factors that could impact the cellular kinetics and efficacy of CAR-T cells include (i) product characteristics such as CAR-T cell subsets (CD4/CD8 ratios 27,32,33 ), phenotypes (T scm , T cm , T em , and T e 28,34 ), and exhaustion markers (PD-1, LAG-3, TIM-3 28,34 ) in patient apheresate and preinfusion products; (ii) presence of immunosuppressive immune cells and soluble factors 35 ; (iii) presence or absence of lymphodepletion 28,29,36,37 ; and (iv) resistance mechanisms leading to antigen escape. 29 These factors are further discussed in the Supporting Information.…”
Section: Multiscale Pk-pd Modeling For Car-t Cell Therapymentioning
confidence: 99%